Intestinal endometriosis amongst other extra-pelvic endometriosis foci presenting as acute/subacute bowel obstruction in women of reproductive age: a retrospective case series study - Ercument Gurluler; Ozgen Isik; Nesrin Ugras; Aysun Sahin; Murat Sen; Tuncay Yilmazlar (BMC Surgery)
Abstract Background This study aimed to investigate the prevalence and clinicopathological correlates of intestinal endometriosis, amongst other extra-pelvic endometriosis foci, presenting as bowel obstruction in general surgery practice. Methods A total of 23 female patients (mean ± SD age: 34.9 ± 6.5 years) who underwent abdominal surgery for acute bowel obstruction and received histopathological diagnosis of endometriosis were included in this retrospective case-series study. Data on patient characteristics, obstetric history, preoperative laboratory and imaging findings, preoperative provisional diagnosis, type of surgical intervention and the pathological diagnosis, and postoperative outcomes were recorded. Results Definitive diagnoses on histopathological work-up involved intestinal endometriosis (52.2%), scar endometriosis (26.0%), ovarian endometriosis (13.0%) and inguinal endometriosis (8.7%). Postoperative complication, reoperation and recurrence rates were 8.7%, 8.7%, and 13.0%, respectively. Intestinal endometriosis, when compared to other extra-pelvic endometriosis foci (scar and inguinal), was associated with significantly higher preoperative platelet counts (332.0(284.0-528.0)vs. 239.0(223.0-370.0) 103/µL, p = 0.010), lower albumin levels (4.0(2.7–4.7) vs. 4.5(4.2–4.9) g/dL, p = 0.029), higher rates of preoperative CT utilization (91.7% vs. 0.0%, p < 0.001) and emergent surgery (83.3% vs. 0.0%, p = 0.001) and longer LOS (median 4.5 (1.0–26.0) vs. 1.0(1.0–1.0) days, p = 0.001) along with a non-significant tendency for higher postoperative complication (16.7% vs. 0.0%) and ICU stay (25.0% vs. 0.0%) rates. Conclusion Our findings revealed intestinal endometriosis, predominantly in the terminal ileum/appendix, was the most common extra-pelvic cause of acute bowel obstruction. The scar endometriosis, inguinal endometriosis and ovarian endometriosis appeared to be other potential but less prevalent aetiologies in this setting.